Yield, Yield Distribution, and Forage Quality of Warm-Season Perennial Grasses Grown for Pasture or Biofuel in the Southern Great Plains. (18th December 2011) - Rogers, James K.; Motal, Frank J.; Mosali, Jagadeesh
Abstract : Fifteen introduced and native warm-season perennial grasses were evaluated for yield, yield distribution, and quality in south-central Oklahoma. These grasses have production potential for forage and/or biofuel. Each was harvested one to four times per year. "Alamo" switchgrass ( Panicum virgatum ) had a two-year average dry matter yield of 17690 kg h a - 1 . Over 1/3 of this production occurred in May with a crude protein (CP) range of 97–115 g k g - 1 . Alamo's high yield potential and early spring growth make it attractive for spring forage production and fall biomass production. Other grasses with two-year average dry matter yields over 11200 kg h a - 1 and 1/3 of yearly production occurring early in the growing season that have potential dual purpose use include "Selection 75" kleingrass ( Panicum coloratum ), "Midland 99" bermudagrass ( Cynodon dactylon ), johnsongrass ( Sorghum halepense ), "Carostan" flaccidgrass ( Pennisetum flaccidum ), and "Ermelo" weeping lovegrass ( Eragrostis curvula ).